Application of the Endoscopic Micro-Inspection Tool QEVO® in the Surgical Treatment of Anterior Circulation Aneurysms—A Technical Note and Case Series - Schebesch, Karl-Michael; Doenitz, Christian; Haj, Amer; Höhne, Julius; Schmidt, Nils Ole (Frontiers in Surgery, 2020)
Introduction The application of neuro-endoscopes in cerebral aneurysm surgery may help to avoid unintended aneurysm remnants and the accidental clipping of perforating arteries and aid the detection of blood collecting in the subdural spaces. Here, we present our experience with the novel endoscopic micro-inspection tool QEVO® (Carl Zeiss Meditec, Germany) in aneurysm surgery. Materials and Equipment In all patients the surgical microscope KINEVO® (Carl Zeiss Meditec, Germany) and the microinspection tool QEVO® were applied. Methods The case series comprises 22 unruptured cerebral aneurysms of the anterior circulation. All aneurysms were treated surgically. All patients routinely underwent computed tomography and digital subtraction angiography within ten days after surgery. Results No aneurysm remnants, cerebral ischemic deficits, or subdural hematomas were detected. Discussion In this technical note, we discuss the benefits and limitations of the QEVO® tool and illustrate the major paradigms by means of intraoperative photographs.